PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CONNECTING, ORGANIZING, REFLECTING, EXTENDING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XII IPA SMAN 2 BATUSANGKAR - Fadhilah, Nurul (Departemen Matematika, 2023)
Understanding of mathematical concepts is the foundation that will help students achieve their learning objectives, thus understanding mathematical concepts becomes an important component in the learning process of mathematics. However, class XII students of the Science Program at SMAN 2 Batusangkar still have a low understanding of mathematical concepts. One of the strategies to overcome this is to modify the learning model, such as the Connecting Organizing Reflecting Extending (CORE) cooperative learning model. The research conducted on class XII IPA students at SMAN 2 Batusangkar aims to find out whether students who understand mathematical concepts using CORE cooperative model are higher than the conventional learning process. This research is a Quasi Experiment with a nonequivalent posttest-only group design. The population is all students of class XII IPA SMAN 2 Batusangkar with samples from class XII IPA 2 and XII IPA 3. The final test of understanding mathematical concepts is used as a research instrument. Keywords– Connecting Organizing Reflecting Extending, Understanding of Mathematical Concep